FGF23 Induction of O-Linked N-Acetylglucosamine Regulates IL-6 Secretion in Human Bronchial Epithelial Cells - Krick, Stefanie; Helton, Eric Scott; Hutcheson, Samuel B.; Blumhof, Scott; Garth, Jaleesa M.; Denson, Rebecca S.; Zaharias, Rennan S.; Wickham, Hannah; Barnes, Jarrod W. (Frontiers in Endocrinology, 2018)
The hexosamine biosynthetic pathway (HBP) generates the substrate for the O-linked -N-acetylglucosamine (O-GlcNAc) modification of proteins. The HBP also serves as a stress sensor and has been reported to be involved with nuclear factor of activated T-cells (NFAT) activation, which can contribute to multiple cellular processes including cell metabolism, proliferation, and inflammation. In our previously published report, Fibroblast Growth Factor (FGF) 23, an important endocrine pro-inflammatory mediator, was shown to activate the FGFR4/phospholipase C (PLC)/nuclear factor of activated T-cells (NFAT) signaling in chronic inflammatory airway diseases such as cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD). Here, we demonstrate that FGF23 increased the O-GlcNAc modification of proteins in HBECs. Furthermore, the increase in O-GlcNAc levels by FGF23 stimulation resulted in the downstream activation of NFAT and secretion of interleukin-6 (IL-6). Conversely, inhibition of FGF23 signaling and/or O-GlcNAc transferase (OGT)/O-GlcNAc reversed these effects. Collectively, these data suggest that FGF23 induced IL-6 upregulation and secretion is, at least, partially mediated via the activation of the HBP and O-GlcNAc levels in HBECs. These findings identify a novel link whereby FGF23 and the augmentation of O-GlcNAc levels regulate airway inflammation through NFAT activation and IL-6 upregulation in HBECs. The crosstalk between theseis signaling pathways may contribute to the pathogenesis of chronic inflammatory airway diseases such as COPD and CF as well as metabolic syndromes, including diabetes.